2003
DOI: 10.1021/ic034554p
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of a Novel 3D Straight-Channel Polyoxovanadate and an Unexpected Trimeric Barbiturate Obtained by Hydrothermal Reactions

Abstract: The hydrothermal reaction of NaVO(3).H(2)O, barbituric acid, NH(2)NH(2).2HCl, H(3)PO(4), and H(2)O gave a novel heteropolyoxovanadate Na(6)[(P(V)O(4))V(V)(6)V(IV)(12)O(39)](2).H(3)PO(4).31H(2)O (1) and an unexpected phase Na(2)[C(12)H(6)N(6)O(9)].7H(2)O (2). The basic building blocks in 1 are the six-capped sphere-shaped heteropoly anion [(P(V)O(4))V(V)(6)V(IV)(12)O(39)](3-) with framework similar to that of the reported polyoxovanadates possessing [V(18)O(42)] clusters encapsulating VO(4) or other ions. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 40 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…The formation of the barbituric acid trimer may be involve in oxidation of the enol form and then radical coupling. 30 The proposed mechanism of the formation of 16b by chemical method is shown in Scheme VI. The 1,3-dimethyl pyrimidine-2,4,5,6(1H,3H)-tetraone (1,3-dimethyl alloxan, 17b) was formed from the oxidation of 1,3-di-methyl barbituric acid 1b.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the barbituric acid trimer may be involve in oxidation of the enol form and then radical coupling. 30 The proposed mechanism of the formation of 16b by chemical method is shown in Scheme VI. The 1,3-dimethyl pyrimidine-2,4,5,6(1H,3H)-tetraone (1,3-dimethyl alloxan, 17b) was formed from the oxidation of 1,3-di-methyl barbituric acid 1b.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the numerous inorganic families and examples of magnetic openframework materials so far described along this review as well as their enormous progress experienced over the last 15 years, the search for new inorganic magnetic open-framework compounds can be still considered at an early stage. Indeed, recent examples of magnetic silicates, 202 germanates, 203 fluorides, 17,204 selenites, 205 polyoxovanadates, 206 sulfides 207 and oxochlorides 16 with open-framework structures seems to confirm such tendency by opening new and successful synthetic routes. From a magnetic point of view, most of them still behave as paramagnets with weak antiferromagnetic interactions at low temperatures.…”
Section: Sulfates the Interest For Magnetic Open-frameworkmentioning
confidence: 94%
“…The construction of porous POM materials is also possible using appropriate inorganic counter cations, and such all-inorganic POM materials are expected to be highly stable under thermal and redox conditions. All-inorganic POMs can be roughly divided into two types: (A) those utilizing ionic bonds or hydrogen bonds between clusters and (B) those linking POMs with covalent bonds. For type A POMs, several examples of aluminum cluster-paired POMs are known. Kwon et al reported all-inorganic porous POMs composed of a cationic aluminum cluster, [Al 13 O 4 (OH) 24 (H 2 O) 12 ] 7+ ({Al 13 } 7+ ), with [Al­(OH) 6 Mo 6 O 18 ] 3– , or [V 2 W 4 O 19 ] 4– .…”
Section: Introductionmentioning
confidence: 99%
“…For type B POMs, Khan et al reported frameworks in which [V 18 O 42 (XO 4 )] 6– (X = V 5+ or S 6+ ) was cross-linked with [M­(H 2 O) 4 ] 2+ (M = Co 2+ or Fe 2+ ) . Yang et al reported a material in which the [(P V O 4 )­V V 6 V IV 12 O 39 ] 3– unit was directly linked through V–O–V bonds . Three-dimensional (3D) Keggin-type POM frameworks with K + and Na + were reported using [SiMo 12 O 40 ] 4– , [SiVW 11 O 40 ] 5– , or [BW 12 O 40 ] 5– .…”
Section: Introductionmentioning
confidence: 99%